Methodology of satellite microwave diagnostics of latitudinal-zonal and seasonal variations of frozen soil and sea ice - V. V. Melentiev; I. V. Matelenok (Лëд и снег, 2015)
In the frame of the work we have had investigated the utility of 6.9GHz dual polarization passive microwave data from the sensor AMSR-E for quantitative assessment of spatial and temporal variations of permafrost, seasonally frozen grounds and sea ice properties along the transect 70° E in 2005–2008 years. Analysis of the factors which could be detected with using study of the spatial-temporal variations of the microwave emissivity (brightness temperatures) of the system «Earth-atmosphere» was carried out with using in situ data obtained from meteorological stations situated along the investigated transect of the Western Siberia and geocryologic station Marre-Sale (Yamal Peninsula). A new method of visualization of the brightness temperatures in spatial-temporal dimensions was suggested and practical applied. Eight latitudinal zones with intrinsic peculiarities of the spatial and seasonal variability of the brightness temperatures were revealed and investigated in many details. Comparison of the location of these zones with geographic distribution of biomes in Western Siberia was provided and it shows that satellite passive microwave information can be used for classification of the territories inside biomes. In frame of this study the annual brightness temperatures course for tundra zone area has been strictly divided into four periods (seasons) characterized by different types of microwave emissivity variations. For boreal needle-leaved forest zone these seasons are manifested weaker. Comprehensive analysis of the satellite microwave survey data and corresponding the in situ data has shown satisfactory correlation between the brightness temperatures of the tundra areas on the Yamal Peninsula and their thermodynamic ground-trough temperatures at the square of geocryologic station Marre-Sale during winter period of stable frozen conditions and vegetation period. In these periods one-channel satellite microwave survey could be applied for the retrieving ground temperatures with using linear regression models.